The Trotula : a medieval compendium of women's medicine - Green, Monica Helen (Middle Ages series., 2001)
"This long-awaited book makes available ... the most important collection of material on women's diseases and their treatments for the period from the twelfth to the fifteenth centuries."--Social History of Medicine